THE USE OF CHATGPT ON STUDENTS’ THESIS WRITING OF ENGGLISH EDUCATION STUDY PROGRAM AT UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Renaldi; Veni Roza; Reflinda Reflinda; Melyann Melani (STKIP Subang, 2026)
This study was conducted to identify AI-generated content in student thesis writing and to investigate the phenomenon of dependence on ChatGPT among students of the English Education Study Program at UIN Sjech M. Djamil Djambek Bukittinggi. The problem arises due to the rapid increase in the use of AI applications such as ChatGPT, while the campus does not yet have official guidelines regarding the use of AI in scientific work and there is a lack of student awareness in using AI responsibly. This situation raises ethical issues, including plagiarism, lack of honesty in acknowledging AI assistance, excessive dependence, and a decline in critical thinking skills. Therefore, this study aims to analyze the problems faced by students when using AI to complete writing assignments. This study used a quantitative descriptive research design, with data collected through document analysis of student theses involving the use of ChatGPT. Seventy-eight thesis documents were selected using purposive sampling techniques, and GPTZero was used as an AI detection tool to identify the level of AI involvement in student writing. The findings show that 75 out of 78 student documents indicate a high level of dependence on ChatGPT, while 3 documents show an acceptable level of AI usage. These results suggest that ChatGPT is often used not only for language refinement but also to generate substantial portions of academic texts, which may hinder students’ independent writing skills, originality, and critical thinking, as well as raise concerns about plagiarism and academic integrity.